A NOVEL ALGEBRAIC EXTRA-STRESS MODEL AND ITS ANALYTIC SOLUTION FOR FULLY DEVELOPED LAMINAR FLOWS - Paulo, Gilcilene S. [UNESP]; Mompean, Gilmar; Oishi, Cassio M. [UNESP]; Tome, Murilo F.; Idelsohn, SR; Sonzogni, V; Coutinho, A.; Cruchaga, M.; Lew, A.; Cerrolaza, M. (Int Center Numerical Methods Engineering, 2015)
This work presents the development of an algebraic extra-stress model (AESM) for modelling viscoelastic flows governed by the constitutive Finite Extendable Non-linear Elastic - Chilcott and Rallison (FENE-CR) differential model. An algorithm for solving the governing equations for incompressible flows of FENE-CR fluids by the AESM model is given. Moreover, by considering fully developed flows, analytic expressions for the conformation tensor A and velocity arc derived. These analytic solutions arc employed to verify the convergence and accuracy of the numerical methodology for simulating flows modelled by this new AESM.
Keywords: FENE-CR Model; Algebraic Model; Analytic Solution; Finite Difference Method